Environmental regulatory calculations handbook - Stander, Leo (John Wiley & Sons, 2008)
"Regulatory Calculations Handbook" addresses the environmental concerns of individuals by presenting the basic fundamentals of many environmental regulatory topics. Featuring an overview of the history of environmental problems, the current regulatory framework, and problems/solutions of practical problems in the field, this handbook comprehensively brings the potential calculations and information on regulations into one single source reference. It: provides 500 solved problems, which detail how to calculate the amount of pollutant that a facility is letting go into the environment; includes problems and solutions that can stand alone, offering material that develops the reader's understanding of regulatory matters; and combines information that is otherwise spread out and difficult to consolidate quickly.
Keywords: Environmental law -- United States.; Environmental policy -- United States.; elektronické knihy; electronic books